A new heteroleptic oxalate‐based compound: poly[[2‐(aminomethyl)pyridine]di‐μ6‐oxalato‐chromium(III)potassium(I)]. Issue 1 (15th January 2014) - Kenfack Tsobnang, Patrice; Wenger, Emmanuel; Ponou, Siméon; Dahaoui, Slimane; Lambi Ngolui, John; Lecomte, Claude
<x xml:space="preserve">Abstract</x> The title compound, [KCr(C2O2)2(C6H8N2)]n, was obtained from aqueous solution and analyzed with single‐crystal X‐ray diffraction at 100 K. It crystallizes in the monoclinic space group C2/c and displays a three‐dimensional polymeric architecture built up by bimetallic oxalate‐bridged CrIII–K helical chains linked through centrosymmetric K2O2 units to yield a sheet‐like alternating P/M arrangement which looks like that of the previously described two‐dimensional [NaCr(ox)2(pyim)(H2O)]·2H2O [pyim is 2‐(pyridin‐2‐yl)imidazole; Lei et al. (2006). Inorg. Chem. Commun.9, 486–488]. The CrIII ions in each helix have the same chirality. The infinite neutral sheets are eclipsed with respect to each other and are held together by a hydrogen‐bonding network involving 2‐(aminomethyl)pyridine H atoms and oxalate O atoms. Each sheet gives rise to channels of Cr4K4 octanuclear rings and each resultant hole is occupied by a pair of 2‐(aminomethyl)pyridine ligands with partial overlap. The shortest Cr...Cr distance [5.593 (4) Å] is shorter than usually observed in the K–MIII–oxalate family.